Intramedullary Osteosclerosis of the Tibia Diaphysis - Ganesh Singh Dharmshaktu; Ajay Kamat; Ishwar Singh Dharmshaktu (Journal of Orthopedics, Traumatology and Rehabilitation)
Intramedullary osteosclerosis (IMOS) is an uncommon clinical entity that represents isolated sclerosis within a segment of the medullary cavity of a long bone. Obliteration of the medullary cavity, in the absence of associated features of common causes such as infection, neoplasm, or injury should arise suspicion of this rare differential diagnosis. Localized pain and swelling, but without any periosteal changes, adjacent soft-tissue edema or bony abnormality, may be suggestive of IMOS. Careful radiological assessment and the use of advanced imaging modalities are important to reach to the appropriate diagnosis. We, hereby, describe a case with pain in the left mid-leg region and showing evidence of a segment of sclerosis within the medullary cavity on both the radiograph and magnetic resonance imaging. Open biopsy was done following the creation of a cortical window and was followed by multiple drilling of the adjacent area of the bone. The pain was dramatically relieved postsurgery and the histopathology reports were suggestive of IMOS. There was neither a recurrence of the symptoms nor any complications reported in the follow-up of 15 months.